Estudo comparativo utilizando lasers de 685 nm e 830 nm no processo de reparo tecidual em tendões tenotomizados de ratos - Carrinho, Patrícia Michelassi (2004)
A lot of therapeutic techniques are used to accelerate and/or stimulate the tendineous repair process, among this techniques we have the low level laser therapy (LLLT). Therefore, this study had the aim of evaluating the effects of LLLT, in different wavelengths and different densities energy, on the tendineous repair process of calcaneal tendon of mice. In this study was used 48 male mice. 40 animals were submitted to the unilateral total tenotomy induced in the middle portion of the right calcaneal tendon. The tendons weren’t sutured after the surgery, just the skin around the surgery. The animals were randomized divided in 3 experimental groups (1, 2 and 3) and each group were divided in two subgroups. The subgroup A was treated with laser of 685 nm, 3 J/cm2, the subgroup B was treated with laser 685 nm, 10 J/cm2, the subgroup C was treated with 830 nm, 3 J/cm2 and the subgroup D with laser 830 nm, 10J/cm2; the subgroups E and F were classifieds as injured control/placebo treatment and non-injured control. It was used the lasers 685 nm and diode GaAlAs (830 nm), the parameters used in both lasers were 15 mW, continuos, power density of 5,4 W/cm2 and doses of 3 J/cm2 and 10 J/cm2. The applications were made punctually in each 24 hours, during 12 consecutive days, in just one point on the injured lesion. All animals were killed on the 13º day after the surgery and the tendons were extracted cirurgically and prepared for qualitative and quantitative analysis carry out through of polarization microscopy for obtain data of state of concentration, aggregation, orientation and deposition of collagen fibers in the site of tenotomy, was used measures of total birefringence take in polarization microscopy. After, it was obtained a picture of each tendon in the polarization microscopy for the qualitative histologic analysis of the tissue. The data analysis were made using the non-parametric test of multiple comparations in order to compare the data of all subgroups. It was found through of difference of OR (nm) values corresponding for the total birefringence that the molecules of collagen of tendons in process of tissue repair answered to the LLLT during the period of data collection, probabily through the increase in the fibroblastic proliferation and collagen synthesis. The tendinous repair of the subgroup A (685 nm, 3 J/cm2) showed the best result, considering the level of tissue organization, orientation, state of macromolecular aggregation and collagen deposition in the site of lesion. This subgroup was statistically different from the other subgroup, because it showed a higher OR value than the other subgroups treated with laser and the subgroup injured control/placebo treatment. We can conclude that, in the conditions our work was developed, there are different organizational answers in the injuried tendineous tissue and treated with LLLT. Therefore, there is a relationship between the improvement in the tendineous repair and the laser parameters used. In this case there were an acceleration of the tendineous repair when used the laser 685 nm and the dose of 3 J/cm2.